2010
DOI: 10.1523/jneurosci.0917-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Defect Is Marked across Multiple Rodent Models of Huntington's Disease and Is Manifest in Astrocytes

Abstract: Brain cholesterol, which is synthesized locally, is a major component of myelin and cell membranes and participates in neuronal functions, such as membrane trafficking, signal transduction, neurotransmitter release, and synaptogenesis. Here we show that brain cholesterol biosynthesis is reduced in multiple transgenic and knock-in Huntington's disease (HD) rodent models, arguably dependent on deficits in mutant astrocytes. Mice carrying a progressively increased number of CAG repeats show a more evident reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
141
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(155 citation statements)
references
References 26 publications
12
141
2
Order By: Relevance
“…9,10,18,50 Additionally, synaptosomes carry suboptimal levels of sterols in early R6/2 model. 8 Here, we showed that a non-cell autonomous cholesterol-handling defect in astrocytes affects cholesterol shuttling between astrocytes and neurons, which has a reversible detrimental effect on synaptic-related parameters in HD neurons.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…9,10,18,50 Additionally, synaptosomes carry suboptimal levels of sterols in early R6/2 model. 8 Here, we showed that a non-cell autonomous cholesterol-handling defect in astrocytes affects cholesterol shuttling between astrocytes and neurons, which has a reversible detrimental effect on synaptic-related parameters in HD neurons.…”
Section: Discussionmentioning
confidence: 81%
“…Quantitative assays confirmed that concentrations of apoE ( Figure 1e) and cholesterol ( Figure 1f) were significantly reduced in conditioned media from Q140/7 astrocytes and from primary R6/2 astrocytes compared with their respective controls. The impairment in apoE release is likely due to reduced synthesis of intracellular apoE as indicated by reduced mRNA and protein levels in YAC128 astrocytes 8 and in R6/2 and HD NS-derived astrocytes (Supplementary Figure 1g).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations